# If ${\tan ^{ - 1}}\sqrt 3 + {\cot ^{ - 1}}x = \dfrac{\pi }{2}$ then find the value of x.

Answer

Verified

360.6k+ views

Hint: To solve this problem we need to have basic knowledge about trigonometric and its values, and also basic calculation for simplifying the values.

Complete step-by-step answer:

Given ${\tan ^{ - 1}}\sqrt 3 + {\cot ^{ - 1}}x = \dfrac{\pi }{2} - - - - - - - > (1)$

We know that ${\tan ^{ - 1}}\sqrt 3 = \dfrac{\pi }{3}$

On substituting the above value in equation (1), we get

$ \Rightarrow \dfrac{\pi }{3} + {\cot ^{ - 1}}x = \dfrac{\pi }{2}$

$ \Rightarrow {\cot ^{ - 1}}x = \dfrac{\pi }{2} - \dfrac{\pi }{3}$

On taking L.C.M we can rewrite the above term as

$

\Rightarrow {\cot ^{ - 1}}x = \dfrac{{3\pi - 2\pi }}{6} \\

\Rightarrow {\cot ^{ - 1}}x = \dfrac{\pi }{6} \\

$

$

\Rightarrow x = \cot \dfrac{\pi }{6} = \sqrt 3 \\

\Rightarrow x = \sqrt 3 \\

$

Therefore the value of $x = \sqrt 3 $.

Note: In this problem we took the ${\tan ^{ - 1}}\sqrt 3 $ value and replaced it in the equation. Later we have simplified the $\pi$ values which is equal to cot inverse x and on further simplification we got x value. In this kind of problem instead of solving the equation it’s better to find the value of the term and simplify.

Complete step-by-step answer:

Given ${\tan ^{ - 1}}\sqrt 3 + {\cot ^{ - 1}}x = \dfrac{\pi }{2} - - - - - - - > (1)$

We know that ${\tan ^{ - 1}}\sqrt 3 = \dfrac{\pi }{3}$

On substituting the above value in equation (1), we get

$ \Rightarrow \dfrac{\pi }{3} + {\cot ^{ - 1}}x = \dfrac{\pi }{2}$

$ \Rightarrow {\cot ^{ - 1}}x = \dfrac{\pi }{2} - \dfrac{\pi }{3}$

On taking L.C.M we can rewrite the above term as

$

\Rightarrow {\cot ^{ - 1}}x = \dfrac{{3\pi - 2\pi }}{6} \\

\Rightarrow {\cot ^{ - 1}}x = \dfrac{\pi }{6} \\

$

$

\Rightarrow x = \cot \dfrac{\pi }{6} = \sqrt 3 \\

\Rightarrow x = \sqrt 3 \\

$

Therefore the value of $x = \sqrt 3 $.

Note: In this problem we took the ${\tan ^{ - 1}}\sqrt 3 $ value and replaced it in the equation. Later we have simplified the $\pi$ values which is equal to cot inverse x and on further simplification we got x value. In this kind of problem instead of solving the equation it’s better to find the value of the term and simplify.

Last updated date: 22nd Sep 2023

•

Total views: 360.6k

•

Views today: 4.60k